Implications of sustainability for the United States light-duty transportation sector. (2016) - Gearhart, Chris
ABSTRACT: Abstract : This paper reviews existing literature to assess the consensus of the scientific and engineering communities concerning the potential for the United States' light-duty transportation sector to meet a goal of 80% reduction in vehicle emissions and examine what it will take to meet this target. Climate change is a problem that must be solved. The primary cause of this problem is burning of fossil fuels to generate energy. A dramatic reduction in carbon emissions must happen soon, and a significant fraction of this reduction must come from the transportation sector. This paper reviews existing literature to assess the consensus of the scientific and engineering communities concerning the potential for the United States' light-duty transportation sector to meet a goal of 80% reduction in vehicle emissions and examine what it will take to meet this target. It is unlikely that reducing energy consumption in just vehicles with gasoline-based internal combustion drivetrains will be sufficient to meet GHG emission-reduction targets. This paper explores what additional benefits are possible through the adoption of alternative energy sources, looking at three possible on-vehicle energy carriers: carbon-based fuels, hydrogen, and batteries.